The Domestic Segment of Global Supply Chains in China under State Capitalism - Tang, Heiwai; Wang, Fei; Wang, Zhi (World Bank, Washington, DC, 2014)
This paper proposes methods to incorporate firm heterogeneity in the standard input-output table-based approach to portray the domestic segment of global value chains in a country. The analysis uses Chinese firm census data for the manufacturing and service sectors, along with constrained optimization techniques. The conventional input-output table is split into sub-accounts, which are used to estimate direct and indirect domestic value added in exports of different types of firms. The analysis finds that in China, state-owned enterprises and small and medium domestic private enterprises have much higher shares of indirect exports and ratios of value-added exports to gross exports compared with foreign-invested and large domestic private firms. Based on input-output tables for 2007 and 2010, the paper finds increasing value-added export ratios for all firm types, particularly for state-owned enterprises. It also finds that state-owned enterprises are consistently more upstream while small and medium domestic private enterprises are consistently more downstream within industries. These findings suggest that state-owned enterprises still play an important role in shaping China's exports.